2005
DOI: 10.1897/05-014r.1
|View full text |Cite
|
Sign up to set email alerts
|

Improved empirical models describing hormesis

Abstract: During the past two decades, the phenomenon of hormesis has gained increased recognition. To promote research in hormesis, a sound statistical quantification of important parameters, such as the level and significance of the increase in response and the range of concentration where it occurs, is strongly needed. Here, we present an improved statistical model to describe hormetic dose-response curves and test for the presence of hormesis. Using the delta method and freely available software, any percentage effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
318
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(331 citation statements)
references
References 36 publications
7
318
2
4
Order By: Relevance
“…According to Cedergreen et al (99), a deficiency of the Brain and Cousens model is that if the slope at the EC50 (β) is smaller than 1 then the model will not yield a curve; therefore they proposed a model that circumvents this drawback. Cedergreen et al (99) provide a robust detection method but it does not estimate the EC50, NOAEL or MSD. In general, a combination of methods may be used to detect hormesis, determine its magnitude and estimate the EC50, NOAEL and MSD, depending on the type of data that is being analyzed and on the behavior of the dose-response curve.…”
Section: Studying Hormesismentioning
confidence: 99%
“…According to Cedergreen et al (99), a deficiency of the Brain and Cousens model is that if the slope at the EC50 (β) is smaller than 1 then the model will not yield a curve; therefore they proposed a model that circumvents this drawback. Cedergreen et al (99) provide a robust detection method but it does not estimate the EC50, NOAEL or MSD. In general, a combination of methods may be used to detect hormesis, determine its magnitude and estimate the EC50, NOAEL and MSD, depending on the type of data that is being analyzed and on the behavior of the dose-response curve.…”
Section: Studying Hormesismentioning
confidence: 99%
“…To investigate the hazard of titanium dioxide Exposure to lower doses of nanoparticles caused a slight increase of root length whereas, root growth was clearly restricted with increasing concentration Lin and Xing (2007) To evaluate the effects of rare earth oxide nanoparticles on root elongation of plants Cerium, lanthanum, gadolinium and ytterbium oxide nanoparticles Rape 0.2 -2000 mg/L At low concentrations (< 0.8 mg/L) lanthanum and ytterbium nanoparticles had positive effects on root elongation but negative effects at higher concentrations Ma et al (2010) using a three parameter log logistic curve fitting with a hormesis parameter added as described by Brain and Cousens (1989) and with a lack of fit model as described by Cedergreen et al (2005), revealed, for the larger nanoparticles (30 nm), a biphasic relationship with a statistically significant stimulation of the algal growth rate at lower concentrations and an inhibition at higher doses. Recently, a study by Mortimer et al (2010), conducted on the ciliated protozoa Tetrahymena thermophila exposed to 31.25, 62.5, 125, 250 and 500 mg/L of copper nanoparticles (Cu-NPs) and to 1.…”
Section: Iavicoli and Othersmentioning
confidence: 99%
“…Growth stimulation due to low doses of different herbicides has been shown in several crop species both in controlled and in the field conditions (Davies et al, 2003;Duke et al, 2006;Cedergreen et al, 2007;Velini et al, 2008). The literature revealed that herbicides at low doses cause on average 20-30% of growth stimulation under controlled conditions (Cedergreen et al, 2007) and 10-25% under uncontrolled field conditions (Cedergreen et al, 2005(Cedergreen et al, , 2009). However, depending on the crop species, type of herbicide and other factors, this average stimulation increased up to 200% (Calabrese, 2008;Velini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%